Performance trade-offs and individual quality in decathletes - Walker, J. A.; Caddigan, S. P. (The Journal of Experimental Biology, 2015)
Many constraints of organismal design at the cell and organ level, including muscle fiber types, musculoskeletal gearing and control-surface geometry, are believed to cause performance trade-offs at the whole-organism level. Contrary to this expectation, positive correlations between diverse athletic performances are frequently found in vertebrates. Recently, it has been proposed that trade-offs between athletic performances in humans are masked by variation in individual quality and that underlying trade-offs are revealed by adjusting the correlations to `control` quality. We argue that quality is made up of both intrinsic components, due to the causal mapping between morpho-physiological traits and performance, and extrinsic components, due to variation in training intensity, diet and pathogens. Only the extrinsic component should be controlled. We also show that previous methods to estimate `quality-free` correlations perform poorly. We show that Wright's factor analysis recovers the correct quality-free correlation matrix and use this method to estimate quality-free correlations among the 10 events of the decathlon using a dataset of male college athletes. We found positive correlations between all decathlon events, which supports an axis that segregates `good athletes` from `bad athletes`. Estimates of quality-free correlations are mostly very small (<0.1), suggesting large, quality-free independence between events. Because quality must include both intrinsic and extrinsic components, the physiological significance of these adjusted correlations remains obscure. Regardless, the underlying architecture of the functional systems and the physiological explanation of both the un-adjusted and adjusted correlations remain to be discovered.